Pengaruh Store Atmosphere terhadap Perilaku Pengunjung Restoran (Studi Kasus :Rumah Makan Inggil dan Madam Wang Secret Garden, di Malang) - Jennifer Charlene Gunawan (Intra, 2017)
The development of people’s lifestyle is adding the function of restaurants. Not only as a place to eat and drink, the restaurant is also a place to socialize, do some works, or meeting with co-workers.The concept of restaurant that joins the retail allowed visitors to do more activities. Malang city is a tourist city and one of the favorite culinary tourism destinations, so there are many restaurants and cafes. Beside taste and price, the main factor that visitors are looking for is the atmosphere. Store atmosphere can be used as a creative strategy to face the intense culinary business competition. The role of interior designers is needed to create an atmosphere through the physical character of exterior buildings and interior spaces that attract attentions, supporting needs, as well as improving visitor convenience. This research reviewed the influence of store atmosphere on visitor behavior in two restaurants with different concepts and merger of retail, named Inggil and Madam Wang Secret Garden Restaurant, Malang. This research used qualitative method. The analysis focused on the forming elements of store atmosphere by Barry Berman and Joel R. Evans which includes exterior, general interior, store layout, and interior point-of-purchase displays.The result shows that store atmosphere influences visitor behaviors. Store atmosphere in Inggil Restaurant allowed visitors to enjoy restaurant, museum, and retail efficiently. Madam Wang Secret Garden's store atmosphere impresses visitors and encourages them to experience all areas inside. Both objects managed to achieve their goals through the establishment of store atmosphere that positively affect the behavior of visitors.